The potential of stable carbon and nitrogen isotope analysis of foxtail and broomcorn millets for investigating ancient farming systems - Dong, Yu; Bi, Xiaoguang; Wu, Rubi; Belfield, Eric J.; Harberd, Nicholas P.; Christensen, Bent T.; Charles, Mike; Bogaard, Amy (Frontiers in Plant Science, 2022)
Foxtail and broomcorn millets are the most important crops in northern China since the early Neolithic. However, little evidence is available on how people managed these two crops in the past, especially in prehistory. Previous research on major C3 crops in western Eurasia demonstrated their potential for revealing the management of water and manure through stable carbon and nitrogen isotope analysis of charred archaeobotanical remains. Here, we evaluate the feasibility of a similar approach to C4 millets. Foxtail and broomcorn millet plants grown in pots under different manuring and watering regimes were analysed to test the effects of management on stable carbon and nitrogen isotope values of grains. Stable nitrogen isotope values of both millets increased as manuring level increased; hence, it appears a feasible tool to identify manuring practices, in agreement with results from recent field studies. However, the two millets exhibit opposing trends in stable carbon isotope values as watering level increased. The shift in stable carbon isotope values of millets is also smaller than that observed in wheat grown in the same experimental environment, making it difficult to identify millet water status archaeologically. In addition, we charred millet grains at different temperatures and for varying durations to replicate macro-botanical remains recovered archaeologically, and evaluate the offsets in carbon and nitrogen isotope values induced by charring. We found that the stable nitrogen isotope values of foxtail millet and broomcorn millet can shift up to 1~2 ‰ when charred, while the stable carbon isotope values change less than 0.3 ‰. Overall, we demonstrate that stable carbon and nitrogen isotope analyses of charred foxtail and broomcorn millet offer potential information on past field management and isotopic reconstruction of diets.